Cinematic-Based Multimedia Web Profile Design For Wesley Elementary School - Wilianto Wilianto (Jurnal Minfo Polgan, 2025)
Technological developments, especially in the field of information and communication, are growing rapidly, including multimedia. This requires educational institutions to develop information media that is appropriate to these developments. Due to the urgent need for more effective and attractive promotions for prospective students, audio-visual media has become an interactive choice and is easily accepted by the public. Wesley Elementary School, to obtain accurate information. The method used by researchers is the Waterfall method. The specifications of the Waterfall method in software or website development include various elements that regulate how the project is carried out from start to finish. At the system analysis stage, an analysis of a system that is currently running at Wesley Elementary School will be carried out to find out existing problems, then plans and solutions will be prepared to solve problems in designing a more effective and efficient system. Then the results will create a school website that is can be accessed by other people. The information system is designed to provide information easily, quickly and accurately so that outsiders can get information. This website profile can help the general public to get wider information about Wesley Elementary School without having to visit the school. It is hoped that future researchers can develop the user interface so that the appearance of the designed web profile can be more attractive and of better quality. In the future, a more updated UI/UX can be developed.